Хазары в Крыму. Хазарское и русское письмо Vl-IX вв. н.э. - Петров, В.П. (Степи Европы в эпоху средневековья, 2001)
The scientific heritage of V.P. Petrov (1894-1969) still remains unknown. Here we present a first print of a manuscript which is part of a larger work that has remained unfinished, and is dedicated to the problem of the origin of the ancient Slavonic written language. The first part of the manuscript bears on putting in good order the written sources about the mission of Byzantine ambassador Konstantine- Cyril to the Khagane of Khazaria. In the second part of the manuscript (theses) the author raises a question about synchronous links of graphic systems in the Vlth- the IXth cc. On the basis of written and archaeological sources he comes to the conclusion that the system of the Old Russian script even older than the Glagolitic or Cyrillic alphabets persisted in Kiev Russ in the IXth- the Xth cc. By its typological features it was close to the Khazarian graphic script.